2005
DOI: 10.1158/0008-5472.can-04-4163
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Signature of Genetic Instability in Colon Cancer

Abstract: Genetic instability plays a central role in the development and progression of human cancer. Two major classes of genetic instability, microsatellite instability (MSI) and chromosome instability (microsatellite stable; MSS), are best understood in the context of colon cancer, where MSI tumors represent f15% of cases, and compared with MSS tumors, more often arise in the proximal colon and display favorable clinical outcome. To further explore molecular differences, we profiled gene expression in a set of 18 co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 42 publications
0
62
0
Order By: Relevance
“…Several studies have examined expression profiles of MSI cancers using DNA microarray. However, these studies either examined MSI cancer cell lines, or the number of MSI cancer samples was comparatively small (8)(9)(10)(11)(12)(13). Furthermore, no studies have highlighted the difference between proximal and distal MSI cancers with regard to gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined expression profiles of MSI cancers using DNA microarray. However, these studies either examined MSI cancer cell lines, or the number of MSI cancer samples was comparatively small (8)(9)(10)(11)(12)(13). Furthermore, no studies have highlighted the difference between proximal and distal MSI cancers with regard to gene expression profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism responsible for MSI is known to be a failure of the DNA mismatch repair system. Recently, whole-genome transcriptional profiling studies have shown that there are profound transcriptional differences between MSS and MSI cancers (Giacomini et al, 2005;Kruhoffer et al, 2005). However, the causal mechanisms for these differences remain unclear.…”
mentioning
confidence: 99%
“…There have been several previous publications describing RERassociated global gene expression changes in CRC using oligonucleotide and cDNA arrays (2,(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jorissen et al (22) published a list of 829 probesets consistently differentially expressed across three independent datasets using primary tissue samples total of 82 RER− cases and 93 RER+ cases, which included the samples analyzed by Watanabe et al (21)(22)(23). Jorissen et al also gave a list of 192 probesets consistently differentially expressed across four independent datasets that included data from 10 RER+ and 10 RER− cell lines (2). All three of the above lists of probesets were downloaded and the corresponding 3′UTR sequences interrogated for the frequencies of mononucleotide repeat lengths, as described in Materials and Methods.…”
Section: Rer-associated Expression Changes Between Crc Cell Lines Arementioning
confidence: 99%